NEK5 promotes breast cancer cell proliferation through up‐regulation of Cyclin A2. Issue 6 (22nd February 2019) - Pei, Jing; Zhang, Jing; Yang, Xiaowei; Wu, Zhengsheng; Sun, Chenyu; Wang, Zhaorui; Wang, Benzhong
Abstract : NEK5, a contraction of NIMA Related Kinase 5, has been shown to regulate the centrosome integrity of cells though; it has been little described in cancer. Herein, to explore the clinicopathological meaning of NEK5 expression in breast cancer, immunohistochemistry was performed to detect the expression of NEK5 on tissue blocks, totaling 203 cases. Quantitative real‐time PCR (qRT‐PCR) was used to evaluate NEK5 mRNA expression with 30 cases of fresh tissues. To observe the function of NEK5 in the growth of breast cancer cells, both MTT and xenografted nude mice were performed. And Transwell assay was employed to observe the variation of migration and invasion. It was shown that up‐regulated NEK5 was significantly associated with tumor progression and poor overall prognosis; and that silencing of NEK5 can significantly suppress the proliferation both in vivo and in vitro, inhibiting migration, and invasion. To get insight into the underlying mechanism by which NEK5 operates in proliferation of breast cancer cells, we showed that NEK5 can up‐regulate Cyclin A2 and down‐regulate Cyclin D1, Cyclin D3, and Cyclin E1 expression. Additionally, Cyclin A2 was also identified as a novel interacting protein for NEK5. Taking together, we firstly defined the oncogenic role of NEK5 in breast cancer that was related to proliferation, supporting that NEK5 might be used a new therapeutic target in breast cancer.